Cellular dosimetry of strontium-90 using the Monte Carlo code MCNPX, detection and X-ray microanalysis. Issue 2 (23rd May 2014) - Hocine, N.; Farlay, D.; Bertho, J.-M.; Boivin, G.; Desbrée, A.; Franck, D.; Agarande, M.
Abstract : The aim of this study is to provide data that increase knowledge about the possible health effects of exposure to 90 Sr contaminant in drinking water. 90 Sr detection in the mouse bone model plays an important complementary role with computational dosimetry in these investigations. S-value (absorbed dose per unit cumulated activity) calculations using Monte Carlo (MC) simulations, 90 Sr detection by liquid scintillation β counting in the femur bone and X-ray microanalysis were carried out. The present work is focused on using MCNPX and its validation at a cellular level. The cytoplasm (Cy), nucleus (N) and 90 Sr radiation source were simulated with the MC code MCNPX. Cells are assumed to be spherical, with the radii of the cell and cell nucleus ranging from 2 to 10 μ m. The S-value (in Gy/Bq.s) calculations were provided for a 90 Sr source distributed uniformly in the cell nucleus or cytoplasm and for two source-target combinations (t←s). A comparison between the calculated MC results and the MIRD values agreed very well since the relative deviations are less than 4%. The earliest results of X-ray microanalysis indicated that the 90 Sr was below the detection limit (<0.1%) in the bone tissue. However, the measurements by liquid scintillation showed the presence of 90 Sr in the femur bone.